Primary signet ring cell carcinoma of the lung: a rare subtype. (20th September 2013) - Livieratos, Speros; Smith, James K; Fatakhov, Eduard; Koch, Christopher F
Abstract : Signet ring cell carcinoma (SRCC) is a subtype of adenocarcinoma. It can arise in different organs including stomach, colon, bladder, prostate and breast. The vast majority of SRCC found in the pulmonary system is metastatic. Primary disease to the lungs is rare. The main feature of this type of malignancy is mucin-producing cells. It has been reported that out of 3500 cases of pulmonary adenocarcinoma, five cases had features of SRCC.